The Role of Parents and Teachers in Parenting Patterns to Improve Critical Thinking Skills in Students - Hasnaa’ Abdillah; Suparmi (Manajia: Journal of Education and Management, 2026)
Currently, we live in the digital era 5.0, which requires us to quickly adapt to technological developments. Life in the 21st century also demands that we possess skills to improve the quality of human resources, one of which is critical thinking. This skill can be developed and is influenced by many factors, including education. This research aims to determine the correlation between the roles of parents, teachers, and parenting patterns as forms of formal and non-formal education in enhancing critical thinking skills. To identify this correlation, a qualitative literature review method was used in this study. The conclusion is that teachers, parents, and parenting patterns are interconnected and mutually supportive in developing children's thinking abilities. As a result, children will be prepared to face globalization and be able to compete with others in many areas in the future.